2022
DOI: 10.1101/2022.04.28.489946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BMAL1 loss in oligodendroglial lineage cells dysregulates myelination and sleep

Abstract: Myelination depends on maintenance of oligodendrocytes that arise from oligodendrocyte precursor cells (OPCs). We show that the dynamic nature of oligodendroglia and myelination are regulated by the circadian transcription factor BMAL1. Bmal1 knockdown in OPCs during development – but not adulthood – decreases OPC proliferation, whereas BMAL1 regulates OPC morphology throughout life. OPC-specific Bmal1 deficiency impairs remyelination in an age-dependent manner, suggesting that age-associated decrements in cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Notwithstanding the known importance of myelination in system-wide neural circuit function, the intrinsic circadian clock control of OPCs, myelin-forming cells, and myelination is quite understudied compared with the circadian regulation of astrocytes and microglia. To date, numerous components of the transcriptional molecular clock have been identified throughout the oligodendroglial lineage in both mice and humans (Zhang Y, et al, 2014(Zhang Y, et al, , 2016Rojo et al, 2022), which has been confirmed at the proteomic level with PER2 staining in oligodendrocytes (Colwell and Ghiani, 2020) and BMAL1 staining in OPCs (Rojo et al, 2022). In addition, isolated OPCs show rhythmic expression of Bmal1, Per2, and Rev-Erbα that is disrupted by the lack of Bmal1 (Rojo et al, 2022).…”
Section: The Interplay Of Circadian and Oligodendroglial Biologymentioning
confidence: 84%
See 4 more Smart Citations
“…Notwithstanding the known importance of myelination in system-wide neural circuit function, the intrinsic circadian clock control of OPCs, myelin-forming cells, and myelination is quite understudied compared with the circadian regulation of astrocytes and microglia. To date, numerous components of the transcriptional molecular clock have been identified throughout the oligodendroglial lineage in both mice and humans (Zhang Y, et al, 2014(Zhang Y, et al, , 2016Rojo et al, 2022), which has been confirmed at the proteomic level with PER2 staining in oligodendrocytes (Colwell and Ghiani, 2020) and BMAL1 staining in OPCs (Rojo et al, 2022). In addition, isolated OPCs show rhythmic expression of Bmal1, Per2, and Rev-Erbα that is disrupted by the lack of Bmal1 (Rojo et al, 2022).…”
Section: The Interplay Of Circadian and Oligodendroglial Biologymentioning
confidence: 84%
“…To date, numerous components of the transcriptional molecular clock have been identified throughout the oligodendroglial lineage in both mice and humans (Zhang Y, et al, 2014(Zhang Y, et al, , 2016Rojo et al, 2022), which has been confirmed at the proteomic level with PER2 staining in oligodendrocytes (Colwell and Ghiani, 2020) and BMAL1 staining in OPCs (Rojo et al, 2022). In addition, isolated OPCs show rhythmic expression of Bmal1, Per2, and Rev-Erbα that is disrupted by the lack of Bmal1 (Rojo et al, 2022).…”
Section: The Interplay Of Circadian and Oligodendroglial Biologymentioning
confidence: 84%
See 3 more Smart Citations